Sleep disturbance and intrusive memories after presenting to the emergency department following a traumatic motor vehicle accident: an exploratory analysis = Alteración del sueño y recuerdos intrusivos después de acudir al departamento de emergencias tras un accidente automovilístico traumático : un análisis exploratorio - Luik, Annemarie; Gebhardt, Isabel (European journal of psychotraumatology, 2019)
Background: Sleep disturbances are common after traumatic events and have been hypothesized to be a risk factor in the development of psychopathology such as that associated with posttraumatic stress disorder (PTSD).Objective: To assess the association between intrusive memories, a core clinical feature of PTSD, and self-reported sleep disturbance shortly after experiencing or witnessing a motor vehicle accident, and whether a brief behavioural intervention (trauma reminder cue and Tetris gameplay) reduced sleep disturbance post-trauma.Method: The exploratory analyses included 71 participants (mean age 39.66, standard deviation 16.32; 37 women, 52.1%) enrolled in a previously published proof-of-concept randomized controlled trial. Participants were recruited from the emergency department after experiencing or witnessing a traumatic motor vehicle accident. Intrusive memories were assessed with a daily paper-and-pen diary for one week post-trauma, and sleep disturbances with three questions from the Impact of Event Scale-Revised assessing problems initiating sleep, problems maintaining sleep and dreams about the event at one week and one month post-trauma. Missing data were imputed 15 times.Results: The total number of intrusive memories during the first week post-trauma suggested weak to moderate pooled intercorrelations with problems initiating and maintaining sleep. An ordinal regression using imputed data suggested that the intervention had no effect on sleep disturbances, while completers only analyses suggested an improvement in problems maintaining sleep at one week.Conclusions: This exploratory study suggested that experiencing early intrusive memories is related to sleep disturbances. Sleep disturbance might be a particularly important construct to assess in studies involving intrusive memories post-trauma.